Key Technologies and Typical Applications in Deepfake Detection - Feng, Bonan (Transactions on Computer Science and Intelligent Systems Research, 2024)
As deepfaking technology advances, it increasingly facilitates the seamless splicing of a person’s voice, facial expressions, and body movements into source images or videos to create hyper-realistic virtual content. This growing technological sophistication, paired with the open-source nature of neural network algorithms, has unfortunately led to the exploitation of deepfake technology by individuals for illicit activities, seeking financial gain. This situation highlights the urgent necessity to thoroughly understand and vigilantly monitor the evolution of deepfake technology. This paper delves into the fundamental concepts and operational mechanisms underlying contemporary deepfake detection methods. It aims to augment the comprehension of these technologies and assesses the strengths and weaknesses of current detection approaches. This evaluation provides critical insights into their operational efficacy and reliability in differentiating genuine from manipulated content. Furthermore, the paper explores the challenges that current technologies face, such as the rapid evolution of deepfake methods that may outpace detection capabilities. By thoroughly analyzing these technologies, the paper endeavors to offer a comprehensive overview and projects future trends in deepfake detection. It anticipates developments that could significantly enhance the efficacy of countermeasures and thus bolster the fight against digital identity fraud and misinformation, safeguarding digital media integrity in an increasingly synthetic landscape.